Materi Pendidikan Akhlak Dalam Pemikiran Burhanul Islam Az-Zarnuji - Abdul Halim; Turmuzi Turmuzi; Tengku Muhmmad Hendra; Kamidan Kamidan; Hasrian Rudi Setiawan (Al-Ulum: Jurnal Pendidikan Islam, 2020)
Studying knowledge is an important process and an obligation for every Muslim. But in his journey it turned out that not all claimants of knowledge are able to master, understand let alone apply the knowledge being studied and obtained. The reasons are diverse, the most dominant one is the neglect of the morality of al-karimah in each of the prosecutors of knowledge. At least, with what was revealed by Burhanu al-islam az-zarnuzi's book. in the muqoddimah of his book ta'lim muta'allim:"When I pay attention to the prosecutors of knowledge in my day, many of them gained knowledge but they were unable to achieve the benefits and fruits of that knowledge (to practice and spread knowledge) they were prevented from doing so. literly, The reason is because they are wrong in taking the path and leaving the conditions. Because every person who takes the wrong path he will get lost, and he will not reach the goal a little or a lot. the terms are: "the loss of manners in the prosecutors of knowledge".it's exacly Therefore, the scholars paid great attention to the problem of manners and morals of the students. So among them said "learn manners before learning knowledge more broadly. Keywords: Material, Moral Education, Burhanul Islam Az-Zarnuji.